Developing Prospective Physical Education Teachers’ Leadership through Community-Based Service-Learning Projects - Hadinata, Reza; Yuliawan, Ely; Daya, Wawan Junresti; Mardian, Roli; Zainuddin, Fadli (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study addresses the limited understanding of how community-based service learning develops leadership as an enacted and contextually shaped practice among pre-service physical education teachers. It explored the leadership-development processes experienced by students enrolled in the Teacher Professional Education Program (PPG) while implementing community-based service-learning projects in Islamic boarding schools. A qualitative multiple-case study design was employed, involving four PPG students who conducted 10-week leadership projects in four Islamic boarding schools in Jambi, Indonesia. Data were collected through semi-structured interviews lasting 45–60 minutes, participatory observations during project implementation, project documents, and participants’ reflective notes. The data were analyzed using team-based thematic analysis supported by NVivo 12 through iterative coding, categorization, comparison, and theme development. The findings showed that participants enacted leadership through stakeholder coordination, role distribution, collaborative communication, negotiation, and adaptive decision-making. These practices were particularly evident when participants responded to limited facilities, structured religious routines, scheduling conflicts, and institutional expectations. Initial difficulties in team management and stakeholder communication became important learning opportunities when participants reflected on their experiences and adjusted their subsequent actions. The Islamic boarding school context therefore functioned not only as the project setting but also as a source of leadership demands that encouraged culturally responsive, adaptive, and collaborative practices. This study provides a process-oriented account of leadership development by demonstrating how contextual demands, situated action, and reflection jointly shape leadership practice. The findings support the integration of structured community engagement, explicit leadership outcomes, and guided reflection into pre-service teacher education programs.